2015
DOI: 10.5861/ijrse.2015.1142
|View full text |Cite
|
Sign up to set email alerts
|

Early years education in Qatar: The good practice guide in theory and practice

Abstract: Qatar's massive education reform, Education for a New Era has dramatically shaped the educational landscape by implementing professional and curriculum standards and introducing best pedagogical practices at all levels. The current concern with Qatar's educational reform is not so much the adopted policies but rather the implementation of these policies into classroom practices. This study examines several kindergartens in Qatar to explore the issues and concerns regarding the implementation of the Supreme Edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Although parental involvement in the education system is critical and needs to be improved, few studies have investigated parental participation in Qatar, as indicated by Al-Thani et al [22]. There are some concerns regarding parents' role and responsibilities in QES as they have become less involved in children's schooling [22].…”
Section: Parental Involvement Models and Theoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Although parental involvement in the education system is critical and needs to be improved, few studies have investigated parental participation in Qatar, as indicated by Al-Thani et al [22]. There are some concerns regarding parents' role and responsibilities in QES as they have become less involved in children's schooling [22].…”
Section: Parental Involvement Models and Theoriesmentioning
confidence: 99%
“…Although parental involvement in the education system is critical and needs to be improved, few studies have investigated parental participation in Qatar, as indicated by Al-Thani et al [22]. There are some concerns regarding parents' role and responsibilities in QES as they have become less involved in children's schooling [22]. Today, parents in Qatar tend to hold full-time jobs, causing them to leave their children with maids/nannies for long periods of time, impacting parents' roles and obligations in their children's education.…”
Section: Parental Involvement Models and Theoriesmentioning
confidence: 99%
See 3 more Smart Citations